A multi‐ingredient dietary supplement abolishes large‐scale brain cell loss, improves sensory function, and prevents neuronal atrophy in aging mice. (20th May 2016) - Lemon, J.A.; Aksenov, V.; Samigullina, R.; Aksenov, S.; Rodgers, W.H.; Rollo, C.D.; Boreham, D.R.
Abstract : Transgenic growth hormone mice (TGM) are a recognized model of accelerated aging with characteristics including chronic oxidative stress, reduced longevity, mitochondrial dysfunction, insulin resistance, muscle wasting, and elevated inflammatory processes. Growth hormone/IGF‐1 activate the Target of Rapamycin known to promote aging. TGM particularly express severe cognitive decline. We previously reported that a multi‐ingredient dietary supplement (MDS) designed to offset five mechanisms associated with aging extended longevity, ameliorated cognitive deterioration and significantly reduced age‐related physical deterioration in both normal mice and TGM. Here we report that TGM lose more than 50% of cells in midbrain regions, including the cerebellum and olfactory bulb. This is comparable to severe Alzheimer's disease and likely explains their striking age‐related cognitive impairment. We also demonstrate that the MDS completely abrogates this severe brain cell loss, reverses cognitive decline and augments sensory and motor function in aged mice. Additionally, histological examination of retinal structure revealed markers consistent with higher numbers of photoreceptor cells in aging and supplemented mice. We know of no other treatment with such efficacy, highlighting the potential for prevention or amelioration of human neuropathologies that are similarly associated with oxidative stress, inflammation and cellular dysfunction. Environ. Mol. Mutagen. 57:382–404, 2016. © 2016 Wiley Periodicals, Inc.